Hydration status in elite wrestlers, judokas, boxers, and taekwondo athletes on competition day - Pettersson, S.; Berg, C. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Weight category athletes are known for practicing rapid weight loss before competition weigh-in. After weigh-in, athletes strive to restore euhydration and body mass through food and fluid intake. The aim of the current study was to assess prevalence of hypohydration at competition time among elite athletes` in four different combat sports, and how water intake and timing of official weigh-in were related to hydration status. Participants were